Beyond “Uniqueness”: Habitual Traits in the Context of Cognitive-Communicative Continuity - Vasilieva, Olga (Theoria et Historia Scientiarum, 2019)
Abstract. The paper discusses a longstanding and prevailing debate in thefields of comparative psychology and language evolution, namely the problem of continuity of cognitive and communicative abilities. It is suggested that although this problem has been addressed by multiple researchers, it remains a persistent topic of discussion and an important meta-theoretical theme in the field of language evolution. To support this claim, the paper first provides a brief overview of the continuity debate by discussing examples of prominent research work in comparative communication and cognition. It further suggests that the problem of continuity can be partly resolved by focusing on cognitive and behavioural trait distribution both between and within species. Specifically, it is proposed that conceptualising given traits as habitual, rather than human-unique, is informative for understanding evolutionary processes shaping human communicative abilities. Finally, the paper suggests that the debate on continuity would benefit from being placed in a broader framework of evolution of phenotypic plasticity and the role of cognition and behavior in evolutionary processes.